PENDIDIKAN KESEHATAN TERHADAP STATUS NUTRISI IBU HAMIL - Husna, Putri Halimu; Murni, Kristia (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
Background: According to the World Health Organization (WHO) Mother's death is still quite high, every day around the world about 808 women die from complications in pregnancy or childbirth. According to WHO, 40% of maternal deaths in developing countries are caused by CED and anemia during pregnancy. Chronic energy deficiency (CED) is a condition where the mother suffers from chronic food shortages (chronic) resulting in the occurrence of health problems in the mother. Pregnant women who have CED five times more risk to give birth to babies with low birth weight (LBW). To know pregnant women have CED or not, measurement were madeof mid-upper arm circumference (MUAC).Purpose: The purpose of this study was to determine the nutritional status of pregnant women who experience the risk of KEK before and after providing health education in Tunggul Giriwono Village, Wonogiri in 2018.Method: This research used a qualitative research with case study research approach.. The population were 16 pregnant women in Tunggul Village, Giriwono Wonogiri Village. In this study researchers took 3 samples of pregnant women multigravida trimester II. Data collection by using interview, observation, measurement of MUAC to know pregnant women have CED risk.Results: The data obtained from measurement of MUAC before health education are informan 1 with MUAC of 22.5 cm, informan II is 23.5 cm and informan III is 22.0 cm. Measurement of MUAC 2 months after health education, the results obtained were MUAC informan I was 24.5 cm MUAC, informan II was 25 cm and MUAC informan III was 24 cm.Conclusion: The results of this study indicate an increase in the nutritional status of pregnant women who experience the risk of CED before and after the provision of health education. The CED prevention program for pregnant women should be carried out well, especially in providing additional food during pregnancy classes and routine MUAC examinations.